A study on some enzymes in ricefield fish as biomarkers for pesticide exposure - Arshad, Juzu Hayati; Muhammad, Mazlina; Ho, Mei Choo; Surif, Salmijah; Mat Jais, Abdul Manan (Malaysian Institute for Nuclear Technology Research, 1998)
A study was carried out on three enzymes in rice field fish which can be used as possible biomarkers for pesticide exposure. The results obtained showed that the activity of the enzyme EROD (ethoxyresorufin-o-deethylase) increased between 1.5-2.2 fold in snakehead or haruan (Channa striata) sampled from the pesticide polluted areas, particularly the recycled areas and only a slight increase in EROD activity in climbing perch or puyu (Anabas testudineus). Increase in the activity of carboxylesterase was also noted. The percentage inhibition of acety1cholinesterase ranges from 18.4%-57.4% and 2.5%-34.2% for Channa striata and Anabas testudineus, respectively. Generally, a higher percentage of acety1cholinesterase inhibition was noted for those fish sampled from the recycled areas. The noted changes in the activity of these enzymes suggest exposure of rice field fish to foreign compounds, possibly pesticides, which are known to induce EROD activity and inhibit acety1cholinesterase activity. Therefore it may be possible to use these enzymes as biomarkers for pesticide exposure.